Effects of Irrigation Water Amount and Humic Acid on β-Glucan Synthesis in Post-Anthesis Grains of Naked Oats - Chunxiang Sun; Qi Wang; Wen Sun; Junying Wu; Shihua Gao; Yandi Liu; Baoping Zhao (Life)
Naked oats offer substantial nutritional and health benefits, primarily due to their main dietary fiber component, soluble β-(1,3)(1,4)-D-glucan (β-glucan). In a pool experiment, humic acid (HA) was applied once during both the booting and anthesis stages at varying irrigation amounts (60 mm, 120 mm, and 180 mm) to assess changes in β-glucan content in grains post-anthesis. Results indicated that at 5 days post-anthesis (DPA), the β-glucan content (3.14% W/W) in grains increased by 16%with the application of HA, compared to the control treatment of spraying an equal volume of water (p < 0.01). The β-glucan content (4.13%, 4.51%) at 15 and 25 DPA reflects increases of 9% and 5% compared to the control. Overall, the application of HA enhanced the β-glucan content in grains, with levels gradually increasing at 5, 15, and 25 DPA; however, the amplitude of the increase gradually declined over time. The β-glucan content in grains at 5 and 15 DPA, along with glucose content in panicles at 20 DPA, directly influenced the β-glucan content in grains at 25 DPA. At 10 DPA, the distribution of sucrose in the leaves and panicles influences the soluble sugar content, subsequently regulating the β-glucan content in the grains at 15 DPA. Specifically, the sucrose content in the leaves exerts a positive regulatory effect, whereas in the panicles exerts a negative regulatory effect.